Trends in State Whistleblowing Laws Following the Whistleblower Protection Enhancement Act of 2012. (June 2022) - Exmeyer, Patrick C.; Jeon, So Hee
Recognizing the importance of whistleblower protection, government has equipped itself with legal tools to protect whistleblowers. At the federal level, the Whistleblower Protection Enhancement Act (WPEA) of 2012 represents the most recent legislative action protecting whistleblowers. Currently, all 50 states have their own whistleblower protection laws. However, given the variations among states in statutory protections for whistleblowers, a need exists to examine important changes to state whistleblower laws in light of larger legislative trends at the federal level. This study addresses this research gap by exploring how state whistleblower protection laws have changed following passage of the 2012 WPEA through the lens of institutional theory. Content analysis findings suggest that post-WPEA state whistleblower laws have adopted changes directly reflecting WPEA provisions. The findings further suggest that post-WPEA state whistleblower laws also contain changes which display loose connection to primary components of the WPEA.